A LITERATURE REVIEW: FACTORS INFLUENCING THE INCIDENCE OF PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY - Rika Triyana; Eko Winarti (Suluh Adiluhung Publisher (SAPub), 2025)
Maternal and child health issues are one aspect that needs attention. One of the problems that arise is pregnant women with chronic energy deficiency (CED) caused by a lack of energy intake from macronutrients and micronutrients. The objective of this study is to analyze factors related to the incidence of CED in pregnant women. The method used a library research method by critically reviewing academic-oriented literature. There were 6 research journals adjusted to the literature review problem. The result showed that the prevalence of chronic energy deficiency risk increased in all age groups and conditions of women (pregnant and non-pregnant). In non-pregnant women aged 15-19 years, the prevalence increased by 15.7%. Likewise, in pregnant women aged 45-49 years, it increased by 15.1%. Suggestions addressed to health workers are expected to increase health education efforts in the form of counseling on the dangers of CED in pregnant women and other materials related to the importance of fulfilling nutrition in pregnant women, as well as increasing community empowerment to achieve coverage of pregnancy checks by health workers.